Assessing the acute effects of diagonal mobilization on static and dynamic balance in young football players: a randomized double-blind study - Studnicki, R.; Taraszkiewicz, M.; Hansdorfer-Korzon, R.; Kawczynski, A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
This randomized double-blind study aimed to assess the acute effects of manual therapy focusing on diagonal sliding (DM) on the static and dynamic balance of young male and female soccer players. Thirty-two regional-level footballers aged between 14 and 16 were randomly assigned to either receive DM or to a control group exposed to a placebo condition. Participants underwent assessment twice: once before the intervention and again afterward. Tests included the single leg lend and hold test and the single leg standing test, measured using force plates. The following variables were recorded: time to stabilization, peak drop landing force, as well as center of pressure (CP) range in the anterior-posterior and medial-lateral directions, and mean velocity while standing on one leg. Significant interactions time × group were found in CP media-lateral (p = 0.003), CP anterior-posterior (p = 0.006), CP mean velocity (p = 0.044), time to stabilization (p < 0.001), and peak drop landing force (p = 0.347;). Within-experimental group analysis (post-pre) revealed significant differences in CP media-lateral (p = 0.001), CP anterior-posterior (p = 0.012), CP mean velocity (p < 0.001), time to stabilization (p < 0.001) and peak drop landing force (p = 0.425). The time to stabilization and the center of pressure range in the anterior-posterior and medial-lateral directions were significantly influenced by the DM intervention. Therefore, it is recommended that individuals involved in clinical or sports settings consider this approach in future analyses. Trial registration: 30/11/2024 ClinicalTrials.gov ID: NCT06719752.